Groundwater-driven paddy farming in West Bengal: how a smallholder-unfriendly farm power policy affects livelihoods of farmers - Shah, Manisha; Shah, Tushaar; Daschowdhury, Sujata (Informa UK Limited, 2022)
West Bengal, India’s largest rice-producing state, has over seven million small and marginal farmers. The rice economy of the region especially that of summer (Boro) paddy is backed by groundwater – an abundant resource in most parts of this State. Despite the rich and shallow aquifers, most of the farmers do not have access to a private source of irrigation and there is a huge dependence on informal irrigation services market where owners of electric tubewells sell irrigation to neighboring farms. Unlike other states of India, West Bengal charges farmers near-commercial metered tariff for the power used to run electric submersible pumps, creating oligopolistic irrigation markets and subsequently leading to exorbitant irrigation costs for small and marginal farmers. This is making paddy farming unviable for many irrigation buyers who are quitting paddy farming altogether. In this chapter, we explore an alternate energy pricing regime with flat-cum-metered electricity tariff structure, which was piloted in Manoharpur village of West Bengal. The pilot throws light into the dynamics of the market players, price setting mechanisms, motivations of pump owners, and provides evidence in support of a flat-cum-seasonally metered tariff structure that has the potential to uplift gains from paddy farming in the State. Without a change in the energy policy of the State, the trend of small farmers leaving agriculture is likely to continue and their livelihoods and food security will continue to be at risk.